Enhanced Electrochemical Property of Surface Modified Li[Co1/3Ni1/3Mn1/3]O2 by ZrFx Coating - Su Hyun Yun; 박용준 (Bulletin of the Korean Chemical Society, 2010)
A Li[Ni1/3Co1/3Mn1/3]O2 cathode was modified by applying a ZrFx coating. The surface-modified cathodes were characterized by XRD, SEM, EDS, TEM techniques. XRD patterns of ZrFx-coated Li[Ni1/3Co1/3Mn1/3]O2 revealed that the coating did not affect the crystal structure of the parent powder. SEM and TEM images showed that ZrFx nano-particles were formed as a coating layer, and EDS data confirmed that ZrFx distributed uniformly on the surface the powder. Capacity retention of coated samples at high C rates was superior to that of pristine sample. However, as the coating concentration increases beyond the optimum concentration, the rate capability was deteriorated. Whereas, as the increase of coating concentration to 2.0 wt %, the cyclic performances of the electrodes under the severe conditions (high cut-off voltage, 4.8 V, and high measurement temperature, 55 oC) were improved considerably. KCI Citation Count: 5